Knowledge Management Practices And Innovation Activities Among Large Manufacturers In Peninsular Malaysia - -, Rosmaini Tasmin (2008)
The objective of this research are (1) to identify the level of KM-enabling practices in large manufacturing firms in Peninsular Malaysia, (2) to examine the differences in KM-enabling practices among large manufacturers in terms of demographics, (3) to examine significant influence of KM-enabling practices on innovation activities by proposing a KM-Innovation model, and (4) to recommend strategic approaches in successful KM implementation, based on the outcomes of this research.